PERAN KARANG TARUNA DALAM MENGATASI KENAKALAN REMAJA UNIT 05 DESA CIMERANG - Putri Tiara; Ageng Saepudin Kanda (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Abstrak. Juvenile Delinquency is a form of inappropriate behavior carried out by teenagers as a result of ignoring existing social norms, which ultimately results in inappropriate behavior. The phenomenon of juvenile delinquency includes all behavior that deviates from norms in society, status violations, and violations of criminal law. Status violations such as running away from home, skipping school, smoking, drinking alcohol, illegal racing, and so on. This research uses a qualitative approach. Data was collected in a natural setting as a direct data source. The results of this research are that the programs implemented by Karang Taruna membership aim to shape the character of teenagers so that they can be responsible for themselves and stay away from things that harm themselves or others. The activities carried out by Rutip every Sunday and Sunday are attended by members of the youth organization, teenagers and the local community. The aim of this activity is to be able to transform teenagers into individuals with character and individuals who have broad knowledge. Therefore, every activity that takes place always emphasizes action or behavior in order to form quality teenage character. Keywords: Behavior, character, delinquency, society, Teenagers